Limited morbidity and possible radiographic benefit of C2 vs. subaxial cervical upper-most instrumented vertebrae - Passias, Peter G. (J Spine Surg, 2019)
BACKGROUND: The study aims to evaluate differences in alignment and clinical outcomes between surgical cervical deformity (CD) patients with a subaxial upper-most instrumented vertebra (UIV) and patients with a UIV at C2. Use of CD-corrective instrumentation in the subaxial cervical spine is considered risky due to narrow subaxial pedicles and vertebral artery anatomy. While C2 fixation provides increased stability, the literature lacks guidelines indicating extension of CD-corrective fusion from the subaxial spine to C2. METHODS: Included: operative CD patients with baseline (BL) and 1-year postop (1Y) radiographic data, cervical UIV ≥ C2. Patients were grouped by UIV: C2 or subaxial (C3-C7) and propensity score matched (PSM) for BL cSVA. Mean comparison tests assessed differences in BL and 1Y patient-related, radiographic, and surgical data between UIV groups, and BL-1Y changes in alignment and clinical outcomes. RESULTS: Following PSM, 31 C2 UIV and 31 subaxial UIV patients undergoing CD-corrective surgery were included. Groups did not differ in BL comorbidity burden (P=0.175) or cSVA (P=0.401). C2 patients were older (64 vs. 58 yrs, P=0.010) and had longer fusions (9 vs. 6 levels, P=0.002). Overall, patients showed BL-1Y improvements in TS-CL (P<0.001), cSVA (P=0.005), McGS (P=0.004). Cervical flexibility was maintained at 1Y regardless of UIV, assessed by CL flexion (−0.2° vs. 6.0°, P=0.115) and extension (13.9° vs. 9.9°, P=0.366). While both subaxial and C2 patients showed BL-1Y improvements in McGS (both P<0.030), C2 patients improved to a larger degree (7.3° vs. 6.2°). Between UIV groups, there were no differences in BL-1Y changes in HRQLs, overall complication rates, or operative complication rates (all P>0.05). CONCLUSIONS: C2 UIV patients showed similar cervical range of motion and baseline to 1-year functional outcomes as patients with a subaxial UIV. C2 UIV patients also showed greater baseline to 1-year horizontal gaze improvement and had complication profiles similar to subaxial UIV patients, demonstrating the radiographic benefit and minimal functional loss associated with extending fusion constructs to C2. In the treatment of adult cervical deformities, extension of the reconstruction construct to the axis may allow for certain clinical benefits with less morbidity than previously acknowledged.